Molecular Diagnostic to Identify Mycobacterial Species in Veterinary Science - De Luna, Carlos Julian; Sparagano, Olivier Andre Ettore (The Thai Journal of Veterinary Medicine, 2015)
The genus Mycobacterium is of utmost importance in veterinary medicine. Members of the genus cause serious diseases to livestock and they also could be transmitted to humans. Bovine tuberculosis, principally caused by M. bovis, is a widespread disease and causes serious economic losses to farmers worldwide. Paratuberculosis or Johne’s disease caused by the M. avium complex, is a slow-developing disease present in several species, particularly cattle, and it has been associated with Chrone’s disease of humans. It causes diarrhoea, and weight loss that could be fatal. The common diagnostic methods used rely upon culturing and microbiological identification of the Mycobacterium involved. However, the pathologically important species of Mycobacterium grow very slowly and could take up to eight to ten weeks to successfully grow on plates. Tuberculin and other immunological response tests are also widespread. However, these techniques also take long time to develop and often they are not conclusive. Recently molecular techniques based on the detection of Mycobacterium nucleic acids and proteins have proven a reliable and more important fast method for the diagnosis of Mycobacterium. Some tests can diagnose the presence of the pathogens in a couple of days. We reviewed the molecular methods available from the scientific literature that have reported to be useful in veterinary science.